PROHIBITED ITEMS DIGITAL INFORMATION TO SUPPORT ACTIVITIES IN THE AIRPORT PASSENGER SECURITY CHECK POINT - Muhammad Afdhal Attaullah (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Penerbangan Palembang, 2025)
This research analyzes the effectiveness of information media related to prohibited items in enhancing the operational efficiency of the Passenger Security Check Point (PSCP) at Terminal 2, Juanda International Airport. The frequent confiscation of items such as liquids, lighters, and scissors, along with the occurrence of long queues, reflects passengers’ limited awareness of carry-on baggage restrictions. The study aims to analyze the strategic placement and effectiveness of information media in improving passenger awareness of security procedures. Using a qualitative method through observations, interviews with Aviation Security personnel and passengers, and field documentation, the study found that the current information media such as posters and digital boards, are placed in non-strategic locations and are therefore ineffective in delivering key messages to passengers. The novelty of this research lies in its focus on evaluating information media placement and its direct impact on the efficiency of PSCP operations. The findings are expected to contribute to improving airport security communication strategies using strategically placed and multilingual digital media, thereby reducing prohibited items and streamlining the security screening process.